The Analysis of the Implementation of 5-S Principles Integrated With ISO 9001 Requirements at Higher Education Level. (August 2019) - Nurcahyo, Rahmat; Apriliani, Fany; Muslim, Erlinda; Wibowo, Alan Dwi
Indonesia, as a country with intensive skill positions, needs to pay attention to the management of colleges. Standardization and development are essential processes in higher education. These can be achieved through the implementation of total quality management (TQM). The initial steps to achieve TQM in higher education are the 5-S kaizen principles ( Seiri/Sort, Seiton/Set in order, Seiso/Shine, Seiketsu/Standardize, dan Shitsuke/Sustain ) and ISO 9000. There are many similarities between the requirements of the quality management system (QMS) standard of ISO 9001 and 5-S principles. Thus, the integration of both systems in higher education is very potential to be implemented. This research was conducted at college Diploma Program. The implementation of 5-S principle integrated with the requirements of ISO 9001 used Analytical Hierarchy Process, Cross-Tabulation Correlation, and Importance Performance Analysis. The results of this research show the priority degree of 5-S principles on ISO 9001 requirements. It is also found that there is a close relationship (correlation value) between each 5-S principle and ISO 9001 requirements, and the results of the performance evaluation of the implementation of the integration system in college.